A New Random Number Generate Algorithm for Cognitive Radio Networks - Li Zhu; Huaqing Mao (2010 International Conference on Computational Intelligence and Software Engineering, 2010)
Cognitive radio networks (CRN) brings rapid development of communication technologies and provides a good solution for heterogeneous networks merging. However, security of CRN becomes the key concern issue. Security of the encryption key is one of the most important factors in communication. Through analysis, we found that: key generation of cognitive radio networks is more dependent on the network environment and terminal users' location information. Therefore, a new random number generate algorithm (ULSI) which is based on users' location information and spectrum information is proposed. This paper mainly analyzes parameter test results and compares ULSI algorithm with PMMLCG, GFSRG, and Super-prime method. Simulation results show that ULSI algorithm has better performance in statistical distribution.